Pengaruh Gaya Kepemimpinan Partisipatif, Budaya Organisasi, dan Lingkungan Kerja Terhadap Kinerja Karyawan PT. Satu Bintang - Tri Yuliantoro; Sampor Ali (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to examine the influence of participative leadership style, organizational culture, and work environment on employee performance at PT. Satu Bintang. The research uses a quantitative approach with a survey method and purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression. The results indicate that the participative leadership style does not have a significant effect on employee performance. In contrast, organizational culture has a positive and significant impact, suggesting that a strong organizational culture can enhance employee productivity and performance. Likewise, the work environment also shows a positive and significant influence on employee performance, highlighting the importance of a supportive and comfortable workplace. Simultaneously, the three variables are proven to have a significant influence on employee performance. These findings suggest that the company should prioritize strengthening its organizational culture and improving work environment conditions. In addition, leadership approaches should be reevaluated to ensure they align with employee needs and organizational goals. This research is expected to serve as a useful reference for companies seeking effective strategies to enhance employee performance through appropriate managerial practices.